How Much Do Tamil Patients With Diabetes Know About Complications of Diabetes? A Descriptive Study - Kisokanth, G.; Prathapan, S.; Indrakumar, J.; Joseph, J.; Arulanandem, K. (My University, 2017)
Introduction: Diabetes mellitus (DM) is a common non-communicable disease (NCD) with numerous short and long term complications. Treatment of diabetes-related complications is costly to the patient and also to the national health structure. The patients who are aware of its complications are more likely to achieve better glycaemic control and to have lesser number of diabetes-related complications. The aim of this study was to assess the knowledge on acute and chronic complications of DM among Tamil patients with type 2 diabetes, attending the medical clinic, Teaching Hospital, Batticaloa, Sri Lanka. Method: This cross-sectional descriptive study was conducted with a patient sample of 384 Tamil patients with type 2 diabetes. Data was collected using a pre-tested interviewer administered questionnaire. Results:The overall knowledge score on diabetes complications ranged from 0-79% with a mean of 28.32% (SD± 16.2%). The majority of the patients were aware that uncontrolled DM could lead to lifelong complications affecting different organs of the body. However, 88.3% obtained less than 50% overall knowledge score on diabetes complications. Around 55% of the participants had identified cataract as a major chronic complication of DM. Sixty percent and 53% of the patients were not able to recognize any symptoms of hypoglycaemia and hyperglycaemia respectively. Conclusion:Knowledge on diabetes complication was very poor among Tamil patients with type 2 diabetes. This highlights the need for better educational programmes on self-awareness on diabetes and related complications in order to reduce the morbidity and mortality pattern of diabetes.
Keywords: Diabetes mellitus; knowledge; acute and chronic complications